PURIFICATION OF NON TOXIC ACIDIC PHOSPHOLIPASE A2 FROM INDIAN COBRA (NAJA NAJA) VENOM - DAYANANDA.K.S; VISHWANATH B.S; SHARATH B.K; GOPINATH S.M (International Journal of Pharma and Bio Sciences, 2013)
Acidic phospholipase A2 (NND-IV-PLA2) was isolated from NajaNaja(Southern India) venom, was purified by anion and cation exchange chromatography. The acidic PLA2 profile of eastern and southern region venom is distinctly different from that of the western regional venom, Southern regional acidic phospholipase A2 did not inducemyotoxicity or anticoagulant activity and didn’t induced edema. However, the acidic PLA2 from all the regions follow the pattern of increasing catalytic activity with increase in the acidic nature of the PLA2 isoforms.